2016
DOI: 10.21048/ijnd.2016.53.4.8396
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Boiling and Juicing on the Content of Polyphenols, Invitro Bioaccessibility and Antioxidant Activity of Commonly Consumed Vegetables and Fruits

Abstract: This study was aimed to investigate the effect of boiling and juicing on selected vegetables and fruits such as carrot, beetroot, tomato, mint leaves, pomegranate and apple. Total and individual polyphenols were evaluated by Folin-Ciocalteu and RP-HPLC. Antioxidant capacities of the selected foods were measured by DPPH, FRAP, ABTS and ORAC assays. In vitro bioaccessibility of total and individual polyphenols were analyzed by mimicking human gastro intestinal system. Results of this study revealed that pomegran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 0 publications
2
5
0
Order By: Relevance
“…At 100 mg/mL, values of percentage scavenging of DPPH were respectively 97; 90 and 80 % for trolox, raw berries extract and boiled berries extract. These results showed the same trend as those of other authors [21,22] who indicated that antioxidant activity via DPPH scavenging of tomato extract and that of Sonneratia apetala fruit significantly decreased from raw to boiled fruit.…”
Section: A Evaluation Of Antioxidant Propertiessupporting
confidence: 90%
See 1 more Smart Citation
“…At 100 mg/mL, values of percentage scavenging of DPPH were respectively 97; 90 and 80 % for trolox, raw berries extract and boiled berries extract. These results showed the same trend as those of other authors [21,22] who indicated that antioxidant activity via DPPH scavenging of tomato extract and that of Sonneratia apetala fruit significantly decreased from raw to boiled fruit.…”
Section: A Evaluation Of Antioxidant Propertiessupporting
confidence: 90%
“…The same trend has been reported for three varieties of green bean [23] and some green vegetables consumed in the Mediterranean diet [24]. On the other hand, Naveena et al [21] obtained the opposite trend with the extract of carrot with a significant increase in the scavenging of the DPPH from raw to boiled carrot. An increase of antioxidant activity via DPPH scavenging was also obtained during boiling of various fruits and vegetables such pumpkin [25], pepper, broccoli, spinach and green beans [26].…”
Section: A Evaluation Of Antioxidant Propertiessupporting
confidence: 70%
“…In generally, the content of total phenolics of the vegetables is significantly affected by cooking style. Results obtained by other authors [Naveena et al, 2016;Wen et al, 2010] indicated that phenolic compounds were sensitive to heat treatment, but Wen et al [2010] and Raikos et al [2018] reported that different types of the cooking process differently affected various vegetables and some combinations of vegetable species/cultivars and heat processing increased their phenolic contents while others decreased them. This phenomenon could be explained by direct interactions between phenolics and some food components or food matrix such as fibre, fat, proteins or carbohydrates, affecting their phenolic content and bioaccessibility [Şengül et al, 2013].…”
Section: Total Phenolic Content and Antioxidant Activitymentioning
confidence: 96%
“…Phenols are responsible for colors in food products and are known for antioxidant activity. During dehulling process, the husk contains some portion of the outer layer of cotyledons and some part of the germ, thus, the husk possesses a remarkable portion of free and hydrolyzable phenolic acids, insoluble dietary fiber (Naveena and Bhaskarachary, 2013) as well as some protein also present in this. These polyphenols exhibit various health benefits due to their anti-inflammatory and antioxidant nature (Scalbert et al, 2005).…”
Section: Total Phenolic Contentmentioning
confidence: 99%